Portable and affordable cold air plasma source with optimized bactericidal effect - Klenivskyi, Myron; Khun, Josef; Thonová, Laura; Vaňková, Eva; Scholtz, Vladimír (Scientific reports, 2024)
The paper reports a low-cost handheld source of a cold air plasma intended for biomedical applications that can be made by anyone (detailed technical information and a step-by-step guide for creating the NTP source are provided). The plasma source employs a 1.4 W corona discharge in the needle-to-cone electrode configuration and is an extremely simple device, consisting basically of two electrodes and a cheap power supply. To achieve the best bactericidal effect, the plasma source has been optimized on Escherichia coli. The bactericidal ability of the plasma source was further tested on a wide range of microorganisms: Staphylococcus aureus as a representative of gram-positive bacteria, Pseudomonas aeruginosa as gram-negative bacteria, Candida albicans as yeasts, Trichophyton interdigitale as microfungi, and Deinococcus radiodurans as a representative of extremophilic bacteria resistant to many DNA-damaging agents, including ultraviolet and ionizing radiation. The testing showed that the plasma source inactivates all the microorganisms tested in several minutes (up to 105-107 CFU depending on a microorganism), proving its effectiveness against a wide spectrum of pathogens, in particular microfungi, yeasts, gram-positive and gram-negative bacteria. Studies of long-lived reactive species such as ozone, nitrogen oxides, hydrogen peroxide, nitrite, and nitrate revealed a strong correlation between ozone and the bactericidal effect, indicating that the bactericidal effect should generally be attributed to reactive oxygen species. This is the first comprehensive study of the bactericidal effect of a corona discharge in air and the formation of long-lived reactive species by the discharge, depending on both the interelectrode distance and the discharge current.
Keywords: Candida albicans; antibakteriální látky; plazmové plyny; Escherichia coli; Anti-Bacterial Agents; Plasma Gases; Staphylococcus aureus